Gambaran Penjualan dan Investası Obat Bermerek Apotek “X” Kelurahan Karang Anyar Kota Tarakan dengan Metode ABC Tahun 2022 - Akbar Syahputra; Benazir Evita Rukaya; Syuhada Syuhada (Journal Borneo, 2024)
Effective drug management requires careful inventory control to prevent problems with shortages or excess stock which can be detrimental to both the pharmacy and consumer service. This research aims to identify the percentage of drugs based on sales and investment transactions using the ABC method at Pharmacy "X" and grouping drugs into categories A, B, or C. This research is retrospective and uses a quantitative descriptive approach. The research object is data on the use of branded drugs at Pharmacy "X" for the period January- December 2022. The sample consists of 897 drug items throughout 2022, and samples were taken using the total sampling method. Data analysis involves marking numbers, item names, types, quantities, units, total prices, and trade groups, which are then sorted based on sales and investment transactions from largest to smallest. ABC analysis of this study shows that Group A dominates drug sales, while Group C has the largest number of drug items despite low movement. Close monitoring is required in Group A to prevent losses due to expired drugs. Pharmacy "X" needs to consider reducing inventory in Group C to optimize expenditure and storage space, thereby reducing the risk of expired medicines and increasing inventory management efficiency.